Age, introduction of solid feed and weaning are more important determinants of gut bacterial succession in piglets than breed and nursing mother as revealed by a reciprocal cross‐fostering model. (21st March 2016) - Bian, Gaorui; Ma, Shouqing; Zhu, Zhigang; Su, Yong; Zoetendal, Erwin G.; Mackie, Roderick; Liu, Junhua; Mu, Chunlong; Huang, Ruihua; Smidt, Hauke; Zhu, Weiyun
Summary: A reciprocal cross‐fostering model with an obese typical Chinese piglet breed and a lean Western breed was used to identify genetic and maternal effects on the acquisition and development gut bacteria from birth until after weaning. Pyrosequencing of 16S rRNA genes results revealed an age‐ and diet‐dependent bacterial succession process in piglets. During the first 3 days after birth, the bacterial community was relatively simple and dominated by Firmicutes with 79% and 65% relative abundance for Meishan and Yorkshire piglets, respectively. During the suckling period until day 14, the piglet breed and the nursing mother lead to increasing differentiation of the fecal bacterial community, with specific bacteria taxa associated with breed, and others with the nursing sow most likely due to its milk composition. Although the effect of nursing mother and the breed were evident through the suckling period, the introduction of solid feed and subsequent weaning were the major events occurring that dominated succession of the gut microbiota in the early life of piglets. This piglet cross‐fostering model is a useful tool for studying the effects of diet, host genetics and the environment on the development and acquisition of the gut microbiota and over longer studies the subsequent impact on growth, health and performance of pigs.